SOME ISSUES OF USING SPECIAL KNOWLEDGE WITHIN CRIMINAL PROCEEDINGS - Bondarenko, O. O. (Bulletin of Kharkiv National University of Internal Affairs, 2018)
The procedural forms of using special knowledge within criminal proceedings have been considered. They include the involvement of an expert, a specialist, the demand and receipt of findings of audits and acts of inspection. The definition of a specialist, expert and forensic expertise has been formulated. It has been noted that the term “a specialist” should be spread to those persons whom the Criminal Procedural Code of Ukraine contains an indication of their professional characteristics and whose special knowledge may be used during the conduction of procedural actions. The procedure of involvement of a specialist in criminal proceedings has been developed. The essence of a forensic expertise has been characterized; and the reasons for its appointment have been provided. The forms of involvement of an expert in criminal proceedings have been analyzed. Thus, they include the request of the party to the criminal proceedings to the expert and his authorization to conduct the examination by an investigate judge or a court. It has been alleged that during the pre-trial investigation a defense party may involve an expert in criminal proceedings by: a) filing a motion to the prosecution party; b) the independent involvement of an expert on contractual terms; c) requesting with the motion on the involvement of an expert to an investigating judge. The victim may on the contrary involve an expert in criminal proceedings only by filing a motion to the prosecution party. In this context, the list of victim’s rights while involving an expert in criminal proceedings needs to be expanded. It is also advisable to regulate questioning of a forensic expert during the pre-trial investigation.